PERAN UMUR PERUSAHAAN DALAM MEMODERASI PENGARUH PROFITABILITAS, LEVERAGE, DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORTS DI PERUSAHAAN TAMBANG - Syahputra Priambudhi (JSE: Jurnal Sharia Economica, 2026)
This research aims to analyze the effect of profitability, leverage, and audit committee on Sustainability Report disclosure with company age as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study employed a quantitative approach using secondary data obtained from annual reports and Sustainability Reports, with a purposive sampling technique resulting in 12 companies and a total of 60 observation data. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software to examine direct and moderating effects among variables. The findings indicate that profitability, leverage, and audit committee have a positive and significant effect on Sustainability Report disclosure. In addition, company age is able to moderate the effect of profitability, leverage, and audit committee on Sustainability Report disclosure. The R-Square value of 0.361 indicates that the research variables are able to explain Sustainability Report disclosure by 36.1%, while the remaining 63.9% is influenced by other variables outside this study